Substituição da adubação nitrogenada mineral pela cama de frango na sucessão aveia e milho - Santos, Loana Bergamo dos (2011)
The constant search for sustainability of production systems have driven research to find alternatives to the problems arising from the intensification of production systems. In this context the present work was to study the effects of substitution of mineral nitrogen by chicken litter in oat and corn in succession and chemical characteristics of soil. Two experiments were conducted during the period from May 2009 to March 2010 in Oxisol area located at the experimental farm of the State University of Paraná, municipality of Rondon. The first test was conducted under a randomized complete blocks with eight treatments obtained from different combinations of chicken manure (applied in oat) and mineral N fertilization (applied in corn) and four replications. We studied the production of dry matter and nutrient accumulation in the straw of the oat crop, and yield components and yield of corn. In the second trial, after the corn harvest, we studied the chemical properties of soil under the design of randomized blocks in factorial scheme 8x3, with the eight combinations of fertilizer used in the first trial related to three depths of soil sampling (0 -5, 5-10 and 10-15 cm). Larger quantities of poultry litter in oat provided higher dry matter production and accumulation of N. All fertilization studied provided satisfactory average productivity for corn (8569 kg ha-1). The soil properties were changed with the use of poultry litter associated with mineral N fertilization. There was a decrease in pH, Ca, Mg, and increased the P, potential acidity, the cation exchange capacity and exchangeable Al with increasing proportions of poultry litter in relation to mineral N fertilization